Relasi Antar Etnis dalam Ruang Multikultural di Pasar Gede Hardjonagoro Kota Surakarta - Muslimin, Faisal Amirul; Gunawan, Gunawan (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2025)
Multiculturalism in Indonesia embodies a complex social framework rooted in colonial history, ethnic mobility, and cultural pluralism. Pasar Gede in Surakarta serves as a crucial site for interaction among various ethnic groups, particularly the Chinese and Javanese communities. These interactions, however, are often challenged by economic disparities and social tensions that can disrupt urban cohesion. Previous studies have primarily focused on multiculturalism through normative frameworks or governmental policies, overlooking the importance of local collective practices. This study aims to identify the factors contributing to cross-ethnic social harmony in Pasar Gede and to explore how social cohesion practices are passed down among diverse trading communities. Utilizing a descriptive qualitative methodology, the research examines spatial distribution, inter-ethnic accessibility, and the daily activities of market participants through field observations and interviews via snowball sampling. Findings reveal that Pasar Gede operates as a communal space managed collectively through informal negotiation and local norms. This study emphasizes that governance based on collective local experiences is more effective in promoting sustainable multiculturalism than top-down approaches. It contributes meaningfully to discussions on spatial studies, ethnic relations, and social cohesion in urban public settings.